Understanding The US' Approach To The Gulf Monarchies From A Historical Perspective: Nixon's Period - (:unkn) unknown (ISTANBUL UNIV, 2019)
The 2017 crisis in the Gulf region, emanating from the claims of Qatar supporting terrorism as well as Iran's regional interferences, created a critical split among the Gulf monarchies. The Trump administration, facing the Saudi Arabia, Bahrain and the United-Arab Emirates line on the one hand, and Qatar on the other, refrained from taking sides and made efforts to appease the tension in a peaceful manner. The purpose of this article is to understand the reasons behind the US' approach to the recent Gulf crisis from a historical perspective. The main argument of the article is that the recent US approach to the 2017 Gulf crisis is derived from the approach adopted by the Nixon administration in the wake of the British withdrawal from the Gulf. The article also argues that the above-mentioned approach constitutes an element of continuity in American foreign policy towards the Gulf. For this purpose, the basic sources used in this work are the declassified documents of American administration on the newly independent Gulf states in the wake of Britain's decision to withdraw from the Gulf. The main questions of the article are what kind of approach the US adopted towards the Gulf in this period that coincides with President Nixon's term, what were the causes of this approach and what kind of connection could be established between then and now.
Keywords: American foreign policy; the 2017 Gulf crisis; The Gulf monarchies; Trump; Nixon; the British withdrawal from the Gulf